Frontiers in Skeletal Muscle Wasting, Regeneration and Stem Cells (2016)
The search for knowledge on cellular and molecular mechanisms involved in skeletal muscle mass homeostasis and regeneration is an exciting scientific area and extremely important to develop therapeutic strategies for neuromuscular disorders and conditions related to muscle wasting. The mechanisms involved in the regulation of skeletal muscle mass and regeneration consist of molecular signaling pathways modulating protein synthesis and degradation, bioenergetics alterations and preserved function of muscle stem cells. In the last years, different kinds of stem cells has been reported to be localized into skeletal muscle (satellite cells, mesoangioblasts, progenitor interstitial cells and others) or migrate from non-muscle sites, such as bone marrow, to muscle tissue in response to injury. In addition, myogenic progenitor cells are also activated in skeletal muscle wasting disorders. The goal of this research topic is to highlight the available knowledge regarding skeletal muscle and stem cell biology in the context of both physiological and pathological conditions. Our purpose herein is to facilitate better dissemination of research into skeletal muscle physiology field.